Chapter 4D Ray-Space and Ultra-Wide Area FTV - Tanimoto, Masayuki (Proceedings e report, 2018)
Ultra-wide area FTV is an FTV with very wide viewing zone where motion parallax is realized. 4D orthogonal ray-space is analyzed and applied to ultra-wide area FTV. Ray-space of "a group of rays through one point" is derived in 4D orthogonal ray-space. It is extended to obtain ray-space captured by linear arrangement cameras. View generation of ultra-wide area FTV needs rays that are not captured by real cameras. These rays are synthesized by interpolating the captured ray-space so that the intersections of the captured ray-space and the ray-space of rays emitted from a light source have the same color.